Fuego cruzado en el debate sobre la prostitución : a propósito del proyecto de ley de "trabajo sexual" para la Argentina - López, Daniela Alejandra (2017)
This essay is, from an abolitionist point of view, a review and a critic on a potential law that aims to regulate "sex work" in Argentina, indicating also potential conflicts with, in case of being passed, the "sex work law" and some of legislation and public policies. It also proposes a public policy on prostitution and points out a method of arguing inside the feminist movement.